2014
DOI: 10.1371/journal.pone.0088033
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Life-History Diversification of an Introduced Fish Species across a Localized Thermal Gradient

Abstract: Climatic variations are known to engender life-history diversification of species and populations at large spatial scales. However, the extent to which microgeographic variations in climate (e.g., those occurring within a single large ecosystem) can also drive life-history divergence is generally poorly documented. We exploited a spatial gradient in water temperatures at three sites across a large montane lake in southwest China (Lake Erhai) to examine the extent to which life histories of a short-lived fish s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 107 publications
(103 reference statements)
1
8
0
Order By: Relevance
“…Similar to common carp in this study, many other introduced species have been shown to rapidly adapt to localized conditions. For example, modified thermal habitats resulted in amphibian evolution after only 36 years (Skelly and Freidenburg 2000) and icefish Neosalanx taihuensis population characteristics rapidly adapted to thermal regimes less than 25 years following introduction (Zhu et al 2014). Clearly, strong selective pressures can result in rapid adaptation of introduced species and similar processes have likely produced the latitudinal variation in population characteristics of common carp documented in this study.…”
Section: Discussionmentioning
confidence: 72%
“…Similar to common carp in this study, many other introduced species have been shown to rapidly adapt to localized conditions. For example, modified thermal habitats resulted in amphibian evolution after only 36 years (Skelly and Freidenburg 2000) and icefish Neosalanx taihuensis population characteristics rapidly adapted to thermal regimes less than 25 years following introduction (Zhu et al 2014). Clearly, strong selective pressures can result in rapid adaptation of introduced species and similar processes have likely produced the latitudinal variation in population characteristics of common carp documented in this study.…”
Section: Discussionmentioning
confidence: 72%
“…For example, Zhu et al. () found that Icefish Neosalanx taihuensis within warmer areas of a mountain lake grew faster and were more fecund than individuals of the same species in colder areas of the lake. Therefore, considering fish populations and their environments as spatiotemporally hierarchical, heterogeneous, and dynamic is necessary for effective fisheries management (Schlosser ; Townsend and Hildrew ; Fausch et al.…”
mentioning
confidence: 99%
“…Heterogeneity in temperature at finer spatial scales from within (e.g., network position and groundwater upwelling; Torgersen et al 1999;Kanno et al 2014;Snyder et al 2015) to among aquatic environments (e.g., between streams and lakes; Lisi et al 2013) may also generate diversity in phenotypic expression. For example, Zhu et al (2014) found that Icefish Neosalanx taihuensis within warmer areas of a mountain lake grew faster and were more fecund than individuals of the same species in colder areas of the lake. Therefore, considering fish populations and their environments as spatiotemporally hierarchical, heterogeneous, and dynamic is necessary for effective fisheries management (Schlosser 1987;Townsend and Hildrew 1994;Fausch et al 2002;Schindler et al 2010).…”
mentioning
confidence: 99%
“…The reproductive cycle of fishes primarily rely on temperature and photoperiod [ 16 , 53 ]. Water temperature can significantly affect breeding processes [ 53 , 54 ] and usually exhibits spatial variations within an aquatic ecosystem [ 54 , 55 ]. In the TGR, the water temperature decreases from the lotic to the lentic zones between March and June, indicating that the water temperature is a key cue for the spawning onset of the three species given the similar photoperiod conditions among the three zones at similar latitude.…”
Section: Discussionmentioning
confidence: 99%
“…Water temperature also affects fecundity and egg size [ 58 , 59 ], and some species of fish tend to exhibit low fecundity in cold environments [ 54 , 60 ]. Our results were inconsistent with those observations, as the highest fecundity was observed in the lotic zone with the lowest water temperature.…”
Section: Discussionmentioning
confidence: 99%